Training in interpersonal skills : tips for managing people at work - Robbins, Stephen P., 1943-; Hunsaker, Phillip L. (Upper Saddle River, N.J. : Pearson, 2012)
By developing and practicing the material in Training in Interpersonal Skills, students can learn how to build productive relationships for any situation. This text also helps students master the skills necessary for personal and organizational effectiveness such as self-management, communication, teaming, and problem solving.
Self-awareness -- Skills : an introduction -- Self-awareness : a point of departure -- Self-management : clarifying values, setting goals, and planning -- Applying emotional intelligence -- Communicating -- Sending interpersonal messages -- Listening and reading nonverbal messages -- Providing feedback -- Communicating across cultures.
Includes index.
1
Keywords: Supervision of employees; Interpersonal communication